MODEL PEMBELAJARAN BERBASIS PROYEK DALAM MEWUJUDKAN PROFIL PELAJAR PANCASILA DI MADRASAH IBTIDAIYAH - Shinta Shibgho Amalia; Iqnatia Alfiansyah (Jurnal Al-Fatih, 2022)
The curriculum is a guideline for the sustainability of an education system with the intention of achieving good learning targets and objectives. The independent curriculum is a learning design that is made in order to feel fun, active and pressure-free learning activities to be able to bring out natural talents that exist in students. The characteristics of an independent curriculum are to develop character according to Pancasila values by applying project-based learning. This research uses qualitative research methods of literature studies. The results of the study in the form of an interview with one of the teachers at the elementary school level said that the independent curriculum is a new innovation in education in Indonesia. The project-based learning model is one of the learning plans that can be an effort in realizing students in having character according to the form of the pancasila student profile. Activities carried out in project-based learning have an influence and linkage to form students according to the 6 dimensions that exist in the profile of pancasila students, namely faith and devotion to God, global diversity, mutual cooperation, critical reasoning, independent and creative. This character has a relationship that can be realized with the habit of applying the PjBL model to learning in elementary schools.